2021
DOI: 10.1186/s12934-021-01603-5
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed mutagenesis of the quorum-sensing transcriptional regulator SinR affects the biosynthesis of menaquinone in Bacillus subtilis

Abstract: Background Menaquinone (MK-7) is a highly valuable vitamin K2 produced by Bacillus subtilis. Common static metabolic engineering approaches for promoting the production of MK-7 have been studied previously. However, these approaches caused an accumulation of toxic substances and reduced product yield. Hence, dynamic regulation by the quorum sensing (QS) system is a promising method for achieving a balance between product synthesis and cell growth. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 65 publications
(72 reference statements)
1
4
0
Order By: Relevance
“…It was found that the synthesis of 1 mol DMK-7 requires 19 mol glycerol and 10 mol NADPH (accompanied by the production of 11 mol NADH). From the overall reaction equation, the higher the production of MK-7, the higher the level of intracellular accumulation of NADH; this conclusion was supported by the findings of a previous study [ 2 ]. However, when the intracellular reducing power is unbalanced, MK-7 synthesis is inhibited, resulting in a decrease in MK-7 levels.…”
Section: Resultssupporting
confidence: 84%
“…It was found that the synthesis of 1 mol DMK-7 requires 19 mol glycerol and 10 mol NADPH (accompanied by the production of 11 mol NADH). From the overall reaction equation, the higher the production of MK-7, the higher the level of intracellular accumulation of NADH; this conclusion was supported by the findings of a previous study [ 2 ]. However, when the intracellular reducing power is unbalanced, MK-7 synthesis is inhibited, resulting in a decrease in MK-7 levels.…”
Section: Resultssupporting
confidence: 84%
“…Triple-fusion PCR was applied for the connection of the upstream DNA sequence, lox71-lox66 cassettes, promoter P D4 sequence, target gene sequence, and downstream sequence. 36 GenScript Biotech (Nanjing, China) was employed to detect the sequence of the PCR fusion fragments. After the sequence validation by GenScript Biotech (Nanjing, China), we integrated the fusion segments into the genome.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In our previous studies, we also found that the formation of wrinkles could promote the connection of channel networks in the membrane and reduce the resistance of liquid ow, so that the pressure in the pipeline was lower than the atmospheric pressure outside. Such a pressure gradient could drive and promote the ow of nutrients through the bio lm (Wu et al 2021) and nally affect the synthesis of the secondary metabolite MK-7. As a nonionic surfactant, PEG-200 does not ionize and generate ions in aqueous solution, possessing the characteristics of wetting and emulsifying.…”
Section: Screening and Optimization Of Surfactantsmentioning
confidence: 99%